In Hospital Outcome of Mitral Valve Replacement with Severe Pulmonary Hypertension - Tumpa, Rubaiya Reza; Ziaul Haque, Al Masum; Hasan, Md Kamrul (Cardiovascular Journal, 2021)
Background: In patients undergoing surgery for mitral valve replacement (MVR) for valvular heart disease, pulmonary artery hypertension (PAH) has been considered a major risk factor. In this prospective study, we have studied the early hemodynamic changes and post-operative outcomes of MVR among patients with mild to severe PAH in Bangladesh perspective. Methods: Total 60 patients who underwent mitral valve replacement for predominantly mitral regurgitation (MR) and mixed lesion with mitral stenosis (MS) having pulmonary arterial hypertension ranging from mild to severe pulmonary artery pressure (PAP) were studied prospectively for immediate postoperative haemodynamic and outcome. The mean age of the patients was 36.23±9.18 years. Total 13 (21.66%) patients had mitral regurgitation and 47 (78.33%) had mixed lesion with mitral stenosis. Patients were divided into two groups based on preoperative pulmonary artery pressures. Group A patients with mild to moderate pulmonary hypertension (PASP 40-59 mm of Hg) and Group B patients with severe pulmonary hypertension (PASPe” 60 mm of Hg). Results: After mitral valve replacement, pulmonary arterial systolic pressure (PASP) decreased significantly in Group A to near normal levels (PASP41.25±7.25). In Group B also the PASP decreased insignificantly (PASP 61.85±9.12) but significant residual PAH remained. Operative mortality was nil (0%) in Group A and 6.7% in Group B. Conclusions: Mitral valve replacement is safe and effective at the presence of PAH as long as the PASP is below or equal to 60 mm of Hg. With PASP >60 mm of Hg, MVR carries a high risk of mortality and the patients continues to have severe PAH in the postoperative period. Cardiovasc j 2021; 14(1): 30-36